2010
DOI: 10.1007/s10533-010-9421-x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic matter composition in a fragmented Mediterranean fluvial system under severe drought conditions

Abstract: In Mediterranean regions, drought is one of the main factors shaping fluvial ecosystems. Droughts cause a shift from lotic to lentic conditions, triggering a gradual fragmentation of the longitudinal hydrological continuum, and a severe alteration of water chemical properties. However, within a biogeochemical perspective, little is known about how and to which extend droughts modify the chemical properties of dissolved organic matter (DOM). In this study, the variability of DOM properties along a fragmented fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 51 publications
5
59
1
Order By: Relevance
“…Hydrologic and biogeochemical differences between pools can contribute to heterogeneity in habitat quantity and quality during dry periods (Fellman et al 2011, Vazquez et al 2011. For example, drying-induced fragmentation concentrates organic matter (Towns 1985, Stanley et al 1997, Caruso 2002, which, when combined with high microbial respiration and low air-water gas exchange rates, can subsequently deplete dissolved oxygen (DO; Acuña et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrologic and biogeochemical differences between pools can contribute to heterogeneity in habitat quantity and quality during dry periods (Fellman et al 2011, Vazquez et al 2011. For example, drying-induced fragmentation concentrates organic matter (Towns 1985, Stanley et al 1997, Caruso 2002, which, when combined with high microbial respiration and low air-water gas exchange rates, can subsequently deplete dissolved oxygen (DO; Acuña et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the loss of NO 3 was compensated by the increase in NH 4 , and in-stream processing did not alter the relative availability of dissolved organic and inorganic N forms. Previous studies in this stream showed that during baseflow or fragmented flow conditions, a high proportion of TDN is available as DON (Bernal et al 2005;Vazquez et al 2011). Interestingly, this balance was interrupted by a sharp increase in DON concentration at the end of the fragmentation phase, probably due to an abrupt microbial biofilm cell lysis or DON exudation under stress conditions (e.g.…”
Section: Temporal Variation In Nutrient Concentrationsmentioning
confidence: 91%
“…During stream expansion after rewetting, high concentrations of nitrogen (N) and phosphorus (P) originate from groundwater inputs and from leaching of accumulated organic material (Tzoraki et al 2007;Obermann et al 2009;Skoulikidis and Amaxidis 2009). The effect of flow intermittency on the fate of organic N and P is less well understood, although an increase in the concentration of dissolved organic N (DON) during stream fragmentation and expansion has been attributed to high microbial production and leaching, respectively (Vazquez et al 2007;Skoulikidis and Amaxidis 2009;Ylla et al 2010;Vazquez et al 2011). Knowledge on the dynamics of organic P is virtually restricted to rewetting periods when the concentration of dissolved organic P (DOP) tends to increase (Tzoraki et al 2007;Skoulikidis and Amaxidis 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Following the rationale of Yu et al (2002) and our observations of increasing protein-like moieties and decreasing molecular weight of DOM with soil depth, we hypothesize that the protein-like fluorescence we observed in groundwater are likely free forms of the proteins. Vazquez et al (2007Vazquez et al ( , 2010 also concluded that proteinaceous DOM associated with groundwater was of low molecular weight.…”
Section: Changes In Dom Concentrations and Quality Across Watershed Smentioning
confidence: 99%